The Effect of Booklets Based on Project Based Learning on Solving Environmental Problems in Junior High Schools - Dwi Prastyo; Fitria Eka Wulandari (Postgraduate, University of Mataram, 2023)
This study aims to inquire about effect of booklets based on project based learning on solving environmental problems in junior high schools. This research is experimental research using One Group Pretest-Posttest design with the subjects of this study being class VII students with a total of 17 students. The collection technique is to inquire the effect of using booklets based on Project Based Learning on solving environmental problems through a test technique where the test is carried out using pretest and post-test design. The instrument in this study was questions with valid and reliable problem-solving indicators using paired sample t-test analysis. The results of this study indicate that there are some effects of booklet on Project Based Learning on environmental problem solving through the pre-test and post-test results on the SPSS 26-assisted paired sample t-test with sig (2-tailed) 0.000 <0.05. Thus, providing booklet learning resources based on Project Based Learning has a significant effect on students' environmental problem-solving abilities.